2009
DOI: 10.1007/s10495-009-0393-z
|View full text |Cite
|
Sign up to set email alerts
|

Partial attenuation of cytotoxicity and apoptosis by SOD1 in ischemic renal epithelial cells

Abstract: Reactive oxygen species (ROS) contribute significantly to apoptosis in renal ischemia-reperfusion (IR) injury, however the exact mechanisms are not well understood. We used novel lentiviral vectors to over-express superoxide dismutase 1 (SOD1) in proximal tubular epithelial (LLC-PK1) cells and determined effects of SOD1 following ATP depletion-recovery, used as a model to simulate renal IR. SOD1 over-expression partially protected against cytotoxicity (P < 0.001) and decreased superoxide (O2•−) in ATP depleted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…In this study, we observed a significant increase of TUNELpositive tubular cells and caspase-3 activity in the rats with renal IRI compared with that in the sham control rats, indicating IRI can trigger the pathways leading to tubular cell apoptosis. ROS has been proposed to initiate apoptosis in renal IRI-induced cells (21). We demonstrate that IMD overexpression significantly reduced the number of TUNEL-positive cells and suppressed caspase-3 activation induced by renal IRI, suggesting that overexpression of IMD inhibits tubular cell apoptosis by reducing oxidative stress.…”
Section: Discussionmentioning
confidence: 62%
“…In this study, we observed a significant increase of TUNELpositive tubular cells and caspase-3 activity in the rats with renal IRI compared with that in the sham control rats, indicating IRI can trigger the pathways leading to tubular cell apoptosis. ROS has been proposed to initiate apoptosis in renal IRI-induced cells (21). We demonstrate that IMD overexpression significantly reduced the number of TUNEL-positive cells and suppressed caspase-3 activation induced by renal IRI, suggesting that overexpression of IMD inhibits tubular cell apoptosis by reducing oxidative stress.…”
Section: Discussionmentioning
confidence: 62%
“…Programmed death of tubular cells is another critical characteristic feature relevant to IRinduced acute renal injury (65). Indeed, IR insult rendered tubular cells undergoing apoptosis along with upregulation of caspase3.…”
Section: Discussionmentioning
confidence: 99%
“…The superoxide dismutase (SOD1) is the main isoform expressed in the kidney. It constitutes the first line of defence against ROS [51]. Since Nox4 is the major source of ROS in the kidneys during the early stages of diabetes, interventions to reduce ROS production by targeting Nox4 or increasing SOD1 may be an attractive therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%